Soil Management Systems: Effects on Soil Properties and Weed Flora - Ferrara, G.; Mazzeo, A.; Matarrese, A.M.S.; Pacifico, A.; Fracchiolla, M.; Al Chami, Z.; Lasorella, C.; Montemurro, P.; Mondelli, D. (South African Journal of Enology and Viticulture, 2016)
A three-year experiment was conducted in order to evaluate the effects of three different soil management systems in a vineyard (organic mulch with exhausted olive pomace at 6 cm thick, weed mowing and herbicide application) on soil physicochemical characteristics and weed flora. A variety of data was collected throughout the trial, such as soil analyses, weed surveys and phytotoxicity tests. The results show that the exhausted olive pomace was able to increase the K and Mg content and exerted good control over weeds, and also had an effect on the weed flora composition. Although further research is needed, it is possible to conclude that the mode of action of the exhausted olive pomace was both mechanical (thickness of the layer) and phytochemical for the release of phytotoxic compounds (allelochemicals).